ТРАНСФОРМАЦІЯ ІНСТРУМЕНТАРІЮ ЗВ’ЯЗКІВ З ГРОМАДСЬКІСТЮ В ЕПОХУ ЦИФРОВОГО МАРКЕТИНГУ - Ольга КУЧКОВА; Віра ЖУРАВЕЛЬ (Herald of Khmelnytskyi National University. Economic sciences, 2026)
The article is devoted to a comprehensive theoretical substantiation and practical analysis of the evolution and transformation of public relations (PR) tools under the influence of modern digital marketing technologies. The paper proves that the rapid development of Internet communications has led to a shift in the classic PR paradigm — from a linear model of monologue "from one to many" through traditional media intermediaries to an interactive, data-centric ecosystem of interaction. The author analyzes in detail the integration model PESO (Paid, Earned, Shared, Owned), which demonstrates the modern merging of communication channels and the transition of PR from a tool solely for building brand awareness to a full-fledged element of the marketing funnel, directly affecting conversion and brand advocacy. Within the framework of practical analysis, the article details the transformational processes of key PR tools: the evolution of paper press releases into multimedia SEO-optimized content, the transition from offline press conferences to interactive digital streams and webinars, the replacement of classic Media Relations with Influencer Relations, and the automation of mention monitoring using artificial intelligence and Social Listening systems. The study is supported by current digital market statistical markers, including data on the integration of AI into daily communication practice (75% of professionals), the scaling of influencer tactics (93%), and the dominance of social networks in the structure of PR strategies (65%). The key features of the modern PR specialist's work are identified: data-centric performance evaluation as opposed to the outdated AVE metric, the need for instantaneous response in real-time (real-time PR), and hyper-targeting of communication messages. Special attention is paid to the concept of Online Reputation Management (ORM) and SERM (Search Engine Reputation Management). The leading trends of digital reputation management (radical transparency, using bloggers as "reputation shields", AI crisis forecasting) are highlighted. Effective integration models are proposed and described: the anti-crisis signal sorting model "Triage", the model of content dominance (Owned-to-Earned), and the model of eco-valence, which links the social responsibility of the brand with performance marketing. It is concluded that the most effective form of modern PR is a continuous synergetic cycle in which digital marketing ensures the collection of accurate data about the audience, and PR forms value messages for digital channels.